HUBUNGAN FUTURE TIME PERSPECTIVE DENGAN CAREER MATURITY PADA MAHASISWA TINGKAT AKHIR - Gwenevere Marvelyn Kounji; Elisabet Widyaning Hapsari (MANASA, 2025)
Final-year higher education students often face career challenges. Career maturity refers to an individual’s readiness to make informed career choices, encompassing all the processes, knowledge, and skills needed to complete career developmental tasks. It is essential for final-year students to achieve career maturity, considering they are nearing the end of their education and transitioning into the future world of work. The purpose of this study was to examine the relationship between future time perspective and career maturity. Future time perspective refers to the extent to which an individual perceives the future according to his or her needs and goals, thus influencing current thoughts, behavior, and decision making. This correlational study, conducted on 166 final-year students in Surabaya selected via incidental sampling. Using the Future Time Orientation Scale and a career maturity scale, Kendall’s Tau-B formula showed that future time perspective was positively related to career maturity. The higher the levels of future time perspective, the higher the levels of career maturity, and vice versa. This suggests final-year students who prioritize future goals are more likely to actively prepare for and achieve career maturity.